Economic Geographical Aspects Of The Formation And Development Of Agglomerations (Eurasian Journal of History, Geography and Economics, 2023)
The article discusses the scientific basis of the emergence of the concept of agglomeration, the formation and development of cities and urban agglomerations, and the current problems in this regard. In particular, the cities of the Fergana Valley, their regional distribution and their characteristics have been scientifically analyzed